Switching From Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide for Human Immunodeficiency Virus Preexposure Prophylaxis at a Boston Community Health Center. (5th August 2021) - Marcus, Julia L; Levine, Kenneth; Sewell, Whitney C; Solleveld, Patricia; Mayer, Kenneth H; Krakower, Douglas S
Abstract: Background: Efforts to end the human immunodeficiency virus (HIV) epidemic may be threatened if limited preexposure prophylaxis (PrEP) resources are funneled from tenofovir disoproxil fumarate with emtricitabine (TDF/FTC) to tenofovir alafenamide with emtricitabine (TAF/FTC) without proportional clinical benefits. Methods: The study population was patients at a Boston community health center who were assigned male sex at birth, aged ≥18 years, and prescribed TDF/FTC for PrEP in the 12 months before TAF/FTC approval (October 2019). We determined the frequency of switching to TAF/FTC in the 12 months after approval, including clinically indicated switching (ie, creatinine clearance <60 mL/minute or reduced bone density), potentially unnecessary switching (ie, no indications for switching and no cardiovascular risk factors), and potentially harmful switching (ie, no indications for switching and either obesity or dyslipidemia). Results: Of 2892 TDF/FTC users, mean age was 38 years, 96.0% were cisgender men, and 78.9% were white. A total of 343 (11.9%) switched to TAF/FTC. Based on documented renal, bone, and cardiovascular risk factors, we identified 24 (7.0%) with clinically indicated switching, 271 (79.0%) with potentially unnecessary switching, and 48 (14.0%) with potentially harmful switching. When indications for switching additionally included hypertension, diabetes, and creatinine clearance 60–70 mL/minute, 27.1% of switching was clinically indicated. Conclusions: Few who switched to TAF/FTC had documented indications for switching, although some appear to have been switched in anticipation of indications developing. As generic TDF/FTC is further discounted, provider education and patient decision aids are needed to facilitate selection of PrEP medications that is both clinically sound and cost-effective. Abstract : In this study from a community health center, 12% of tenofovir disoproxil fumarate/emtricitabine users switched to tenofovir alafenamide/emtricitabine. Lower creatinine clearance was associated with switching, while switching was less likely among those with dyslipidemia.